Population dynamics and demographic structure of Juniperus Phoenicea L. in Semi-Arid North African ecosystem - Benabderrahmane, Ahlame; Belhadj, Safia; Daoudi, Belkacem; Khadoumi, Amar; Boumakhleb, Abdallah; Belhouadjeb, Fathi Abdellatif (Edelweiss Applied Science and Technology, 2025)
The present study aims to characterize the demographic structure of the red juniper (Juniperus phoenicea L.) population under a semi-arid bioclimate in the Central Saharan Atlas Mountains (North Africa) to define its dynamics and predict its future status and conservation. Based on ten selected homogeneous sites, a total of 100 temporary observation plots, each covering 400 m², were surveyed. Within each plot, dendrometric variables (Total height, density) were measured to establish demographic analysis and a static life table. Data analysis revealed that the studied Juniperus phoenicea populations fall into three contrasting "ecological types": expanding populations, self-sustaining populations with natural regeneration, and declining populations. The persistence of the latter is mainly due to the species’ relatively long lifespan, allowing natural renewal to be maintained and ensuring that the population size remains stable at a certain point in the future.